Vertebroplasty in Patients with Severe Vertebral Compression Fractures: A Technical Report - O'Brien, James P.; Sims, Jon T.; Evans, Avery J. (American Journal of Neuroradiology, 2000)
Summary: Vertebroplasty is a procedure in which polymethylmethacrylate (PMMA) is injected into a vertebral body compression fracture. It has been suggested that fractures greater than 65% to 70% of the original vertebral body height are too compressed to be treated successfully with this procedure. We describe six patients with severe compression fractures that were successfully treated with vertebroplasty in which the trocar was inserted in the far lateral aspect of the vertebral body, because of the typical morphology of severe compression fractures.